2020
DOI: 10.1094/pdis-09-19-1979-re
|View full text |Cite
|
Sign up to set email alerts
|

Olive Twig and Branch Dieback in California Caused by Cytospora oleicola and the Newly Described Species Cytospora olivarum sp. nov.

Abstract: Field surveys conducted throughout California olive-growing regions in 2008 and 2009 resulted in a collection of 101 Cytospora-like isolates from olive twig and branch dieback symptoms. Cytospora isolates were isolated from multiple cvs. in different olive orchards in Fresno, Madera, Merced, Napa, Riverside, Santa Barbara, Sonoma, Tulare, and Ventura counties. Taxonomic studies of macro- and microscopic structures along with multigene phylogenetic analyses of the internal transcribed spacer region, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 28 publications
0
24
0
1
Order By: Relevance
“…Other recent reports concern Diaporthe ambigua causing twig cankers in Italy [ 52 ] and Neofabraea kienholzii causing leaf and shoot lesions in California [ 53 ], while Cytospora pruinosa recovered from plants showing branch dieback symptoms in Spain was found not to be pathogenic [ 54 ]. Notwithstanding, reports concerning Cytospora [ 30 , 35 ] must be taken with caution, considering recent assessments of pathogenicity on olive tree by a few Cytospora spp., including the novel species C. olivarum [ 55 , 56 ].…”
Section: Occurrence and Ecological Implications Of Endophytic Fungmentioning
confidence: 99%
“…Other recent reports concern Diaporthe ambigua causing twig cankers in Italy [ 52 ] and Neofabraea kienholzii causing leaf and shoot lesions in California [ 53 ], while Cytospora pruinosa recovered from plants showing branch dieback symptoms in Spain was found not to be pathogenic [ 54 ]. Notwithstanding, reports concerning Cytospora [ 30 , 35 ] must be taken with caution, considering recent assessments of pathogenicity on olive tree by a few Cytospora spp., including the novel species C. olivarum [ 55 , 56 ].…”
Section: Occurrence and Ecological Implications Of Endophytic Fungmentioning
confidence: 99%
“…from almost 30 % of twig dieback and canker samples. Pathogenicity trials illustrated the ability of C. oleicola and C. olivarum to cause lesions when inoculated on olive branches ( Úrbez-Torres et al 2020 ); however, the reported lesion size was considerably smaller than that reported for some species of Botryosphaeriaceae by Úrbez-Torres et al (2013) . In Italy, Pleurostoma richardsiae , Phaeoacremonium spp., and members of the Botryosphaeriaceae have been identified as the most prevalent fungi associated with olive decline ( Carlucci et al 2013 , 2015 , Nigro et al 2013 ).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the above-mentioned pathogens, species of Basidiomycota , Botryosphaeriaceae , Cytospora , Diaporthe , Diatrypaceae , Phaeoacremonium , Phaeomoniellales , and some other fungi such as Comoclathris incompta (= Phoma incompta ), and Pleurostoma richardsiae , have also been associated with various decline-related symptoms of olive trees in Croatia, Greece, Italy, New Zealand, Spain, and the USA ( Rumbos 1988 , 1993 , Taylor et al 2001 , Carlucci et al 2008 , 2013 , 2015 , Moral et al 2010 , 2017 , Kaliterna et al 2012 , Nigro et al 2013 , Úrbez-Torres et al 2013 , 2020 , Lawrence et al 2018 ). Úrbez-Torres et al (2013) identified 18 fungal species in a survey of fungi causing olive twig and branch dieback in California (USA), of which the Botryosphaeriaceae were found to be the most prevalent, followed by species of Diaporthe and the Diatrypaceae .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations